Modern Tendencies of Ensuring International Integration of Sciences in Primary Schools - Sanakulov Xamrakul Rizakulovich; Niyazmetova Nargiza Bakhramovna (Genius Journals, 2022)
The article summarizes the findings on the basis of scientific data and research on ensuring interdisciplinary integration in the field of education, in particular at the primary level of general secondary education.
Keywords: Integration; elementary sciences; education system; school